Penentuan Jalur Evakusi Banjir di Kelurahan Bidara Cina - M Reggi Pahlepi; Rayuna Handawati; Fauzi Ramadhoan A’Rachman (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The research investigates flood evacuation routes in China Bidara Kelurahan, Jatinegara district, East Jakarta City. Quantitative descriptive methods are used in this study. This scripts data collection is carried out through road network analysis, service area, and route analysis using Geographic Information System (SIG). Flood posko area adjusted and community validation compared. The results of the study showed that of the 24 flood evacuation routes, 11 routes were in good condition, 13 roads were blocked by wild parking on the road, and 8 routes of the entire flood escape route had difficult conditions to pass. Validation analysis of communities with processing analysis that has an equation of 80%, and 10 flood posko points scattered in 9 RWs that are flood-prone in the Chinese Flood Field.